2013
DOI: 10.4183/aeb.2013.33
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic administration of anabolic androgenic steroids and taurine on platelet aggregation in rats

Abstract: Background. The pro-thrombotic potential of the anabolic androgenic steroids (AAS), worldwide misused substances, has increasingly become a subject of current interest. Conversely, taurine, a sulfur-amino acid ubiquitous in human body, in addition to other beneficial effects, is thought to have an inhibitory effect on platelet aggregation.Purpose. To assess platelet aggregation both taurine and high doses of AAS were simultaneously chronically administered in rats.Methods. The experiment was conducted on 40 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The current study found an increase (P ≤ 0.05) in platelet number, indicating that increasing platelet number with anabolic steroids increases the risk of cardiovascular disease (Achar, 2010), and that reducing and sealing vascular slits with sulphur amino acid alturin (Taurine) with activated platelets can reduce and seal those risks (Rosca et al, 2013), which were likely associated with proper elevation number of hemoglobin. The findings of the study corroborate those of McCrohon et al,(2000), who found an increase in the average number of platelets as a result of athletes' usage of steroids…”
Section: Sustanon's Effect On Blood Componentssupporting
confidence: 48%
“…The current study found an increase (P ≤ 0.05) in platelet number, indicating that increasing platelet number with anabolic steroids increases the risk of cardiovascular disease (Achar, 2010), and that reducing and sealing vascular slits with sulphur amino acid alturin (Taurine) with activated platelets can reduce and seal those risks (Rosca et al, 2013), which were likely associated with proper elevation number of hemoglobin. The findings of the study corroborate those of McCrohon et al,(2000), who found an increase in the average number of platelets as a result of athletes' usage of steroids…”
Section: Sustanon's Effect On Blood Componentssupporting
confidence: 48%
“…Using Born aggregometric method, we demonstrated that taurine (2% supplemented in drinking water) can decrease platelet aggregation in either normal rats, or in those concomitantly receiving a supraphysiological AAS (anabolic androgenic steroids) dose (10 mg/kg, weekly intragluteal injection, for 3 months) [133]. In a following thromboelastographic (TEG) experiment assessing shear elasticity of the clotting blood, we detected a slight tendency (without reaching statistical significance) of taurine to decrease maximal clot strength and stability in either normal or mixed treated group of rats [134].…”
Section: Evidence From Animal Studiesmentioning
confidence: 99%
“…This is consistent with other findings we have reported. Using the thromboelastographic method to analyze changes in the shear elasticity of clotting blood, supraphysiological DECA administration in rats showed an increase in maximal clot strength and stability (MA), which largely depends on platelet function (platelet bonding via GP IIb/IIIa) [ 153 ].…”
Section: Influence Of Exogenous Androgens On Platelet Hemostatic Amentioning
confidence: 99%